Exercise training improves obesity‐related lymphatic dysfunction. (9th April 2016) - Hespe, Geoffrey E.; Kataru, Raghu P.; Savetsky, Ira L.; García Nores, Gabriela D.; Torrisi, Jeremy S.; Nitti, Matthew D.; Gardenier, Jason C.; Zhou, Jie; Yu, Jessie Z.; Jones, Lee W.; Mehrara, Babak J.
Abstract : Key points: Obesity results in perilymphatic inflammation and lymphatic dysfunction. Lymphatic dysfunction in obesity is characterized by decreased lymphatic vessel density, decreased collecting lymphatic vessel pumping frequency, decreased lymphatic trafficking of immune cells, increased lymphatic vessel leakiness and changes in the gene expression patterns of lymphatic endothelial cells. Aerobic exercise, independent of weight loss, decreases perilymphatic inflammatory cell accumulation, improves lymphatic function and reverses pathological changes in gene expression in lymphatic endothelial cells. Abstract: Although previous studies have shown that obesity markedly decreases lymphatic function, the cellular mechanisms that regulate this response remain unknown. In addition, it is unclear whether the pathological effects of obesity on the lymphatic system are reversible with behavioural modifications. The purpose of this study, therefore, was to analyse lymphatic vascular changes in obese mice and to determine whether these pathological effects are reversible with aerobic exercise. We randomized obese mice to either aerobic exercise (treadmill running for 30 min per day, 5 days a week, for 6 weeks) or a sedentary group that was not exercised and analysed lymphatic function using a variety of outcomes. We found that sedentary obese mice had markedly decreased collecting lymphatic vessel pumping capacity, decreased lymphatic vessel density, decreased lymphatic migration of immune cells, increased lymphatic vessel leakiness and decreased expression of lymphatic specific markers compared with lean mice (all P < 0.01). Aerobic exercise did not cause weight loss but markedly improved lymphatic function compared with sedentary obese mice. Exercise had a significant anti‐inflammatory effect, resulting in decreased perilymphatic accumulation of inflammatory cells and inducible nitric oxide synthase expression. In addition, exercise normalized isolated lymphatic endothelial cell gene expression of lymphatic specific genes, including VEGFR‐3 and Prox1 . Taken together, our findings suggest that obesity impairs lymphatic function via multiple mechanisms and that these pathological changes can be reversed, in part, with aerobic exercise, independent of weight loss. In addition, our study shows that obesity‐induced lymphatic endothelial cell gene expression changes are reversible with behavioural modifications. Key points: Obesity results in perilymphatic inflammation and lymphatic dysfunction. Lymphatic dysfunction in obesity is characterized by decreased lymphatic vessel density, decreased collecting lymphatic vessel pumping frequency, decreased lymphatic trafficking of immune cells, increased lymphatic vessel leakiness and changes in the gene expression patterns of lymphatic endothelial cells. Aerobic exercise, independent of weight loss, decreases perilymphatic inflammatory cell accumulation, improves lymphatic function and reverses pathological changes in gene expression in lymphatic endothelial cells.